Peranan Prajuru Adat Dalam Pelaksanaan Upacara Ngusaba Nyepeg Penjor Di Desa Adat Gebog Satak Tiga Buungan Bangli - Purniati, Kadek (Jayapangus Press, 2022)
The implementation of the Ngusaba Nyepeg Penjor ceremony in the Gebog Satak Tiga Buungan Traditional Village is unique and does not exist in other traditional villages and is inseparable from the role of Prajuru Adat. Ngusaba Nyepeg Penjor ceremony is a form of ritual that aims to invoke prosperity and success in agriculture by the people of Gebog Satak Tiga Buungan. This research aims to find out the ceremony procession, position, role and strategy of Prajuru Adat in Ngusaba Nyepeg Penjor ceremony in Gebog Satak Tiga Buungan Traditional Village. The method used in this research uses a qualitative approach and data collection is done by observation, interviews, literature, and documentation. The results obtained in the research are (1) The procession of Ngusaba Nyepeg Penjor Ceremony consists of Matur Piuning, Nunas Sela, Mecaru, Nunas Tirtha Kekuluh, Ngemedalang Ida Bhatara from Buungan, Ngemedangang Ida Bhatara Lingsir, Ngadegang Jro Pasek, Ngemedalang Ida Bhatara Ring Soang-soang, Melasti, Ageng Canang, Puncak Ngusaba Nyepeg Penjor, Ageng Penek, Nganyarin, Memasar, Bhakti Dewa Hyang, Ida Bhatara Ngeluhur. (2) The position and role of Prajuru Adat in the implementation of the ceremony, namely as the executor of leadership, communicator, facilitator and role model of the community. (3) The strategy of Prajuru Adat in the implementation of the ceremony is to function the existing devices or structures and ensure that it runs well, optimize community support, involve all components of the community and carry out the ceremony according to the community's ability.